PROSES PENGANGKATAN PEMUDA SARJANA PENGGERAK PEMBANGUNAN DI PEDESAAN (PSP-3) PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI RIAU - Putri, Rike Helda; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Undergraduate Program of Rural Development Drivers (PSP-3) is one of the leading programs of Riau Province Youth and Sport Office. The program was developed with the aim of accrediting development through the role of Mentoring, Self-Reliance and Youth pioneering in various youth activities. Through this Rural Development Driving Undergraduate Program (PSP-3), it is expected to strengthen the commitment of the undergraduate youth to build the village progress and make it a place to improve the living standard of the community in the future. The PSP3 program has been underway since 1989 under the name of the Rural Development Enabler program (PSP-3) and has now placed undergraduate degree approximately 18,173 people spread throughout Indonesia. For example, during 2006-2013, the PSP3 Program has reached 2478 villages, 1249 sub-districts and 440 districts. (Legal Basis of PSP 3 of Regional Regulation Number 19 Year 2001) This study aims to: To find out the process of Appointment of Youth Undergraduate Rural Development Drivers (PSP-3) On the Department of Youth and Sports Riau Province. To know and analyze the obstacles of the process of appointment of Youth Undergraduates of Rural Development (PSP-3) in Riau Province Youth and Sports Agency, this research was conducted at Dinas Pemuda dan OlahragaProvinsi Riau, while the result of this research is known that the Appointment of Youth Development Rural (PSP-3) On the Office of Youth and Sports of Riau Province is lacking in publication so that there are still many people or youth who do not know it and obstacles in the implementation System announcement in the acceptance of PSP 3 is less known by the community, especially youth and Reporting made by Participants are inadequate because it is only a general activity report only Keyword: Acceptance, PSP3 Program